2011
DOI: 10.1002/ejic.201100411
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Electron Transfer Dynamics of Two Newly Synthesized Catecholate Bound RuII Polypyridyl‐Based Sensitizers on TiO2 Nanoparticle Surface – A Femtosecond Pump Probe Spectroscopic Study

Abstract: Two new catecholate-bound Ru II -polypyridine based sensitizers, (2,2Ј-bipyridine) (6) with secondary electron-donating groups (tyrosine and phenol, respectively) were synthesized and characterized. Steady-state optical absorption and emission studies confirm strong coupling between the sensitizers and TiO 2 nanoparticles. Femtosecond visible transient absorption spectroscopy has been employed to study interfacial electron transfer (IET) dynamics in the dye-nanoparticle systems to explore the influence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 85 publications
5
18
0
Order By: Relevance
“…From the absorption spectrum with TiO 2 , the configuration of the absorption spectrum is similar to the original spectrum of 2 ( Figure 2D). The attachment to TiO 2 led to quenching of emission ( Figure 2E), which is in agreement with literature reports, 31 and indicates that electrons injected from the excited state of 2 to the conduction band of TiO 2 . The TEM image ( Figure 2F) clearly shows the presence of colloidal particle 5 attached to the semiconductor surface.…”
Section: Pt(ii) Complexes As Photosensitizers For Hydrogen Evolutionsupporting
confidence: 92%
“…From the absorption spectrum with TiO 2 , the configuration of the absorption spectrum is similar to the original spectrum of 2 ( Figure 2D). The attachment to TiO 2 led to quenching of emission ( Figure 2E), which is in agreement with literature reports, 31 and indicates that electrons injected from the excited state of 2 to the conduction band of TiO 2 . The TEM image ( Figure 2F) clearly shows the presence of colloidal particle 5 attached to the semiconductor surface.…”
Section: Pt(ii) Complexes As Photosensitizers For Hydrogen Evolutionsupporting
confidence: 92%
“…Ghosh, Das, and coworkers have investigated in detail the photoexcitation and relaxation kinetics of several catechol-anchored metallo-organic Ru-based dyes [175]. Similar results have been observed recently for Ru II -dyecatecholate complexes with other conjugated electron-donating moieties [182]. Similar results have been observed recently for Ru II -dyecatecholate complexes with other conjugated electron-donating moieties [182].…”
Section: Dye-sensitized Solar Cellssupporting
confidence: 76%
“…Our earlier investigations reveal that the transient absorption spectra for complex ‐TiO 2 are mainly due to charge‐separated species (ie. cation radical and injected electron) and the contribution of excited states is negligible . Our group and many other research groups reported that the conduction band electrons can be detected by the characteristic absorption in visible, near‐IR and mid‐IR region …”
Section: Resultsmentioning
confidence: 64%
“…The excited state relaxation processes consist of internal conversion (IC), intersystem crossing (ISC) and vibrational relaxation (VR). Previous studies on transient spectroscopy state that the femtosecond injection is characteristic feature of the nonthermalized 1 MLCT excited state whereas picosecond injection occur via thermalized 3 MLCT excited state . The transient spectra of complexes 1–3 at each time delay show difference positive absorption (▵A) at higher wavelength ∼500‐800 nm along with difference negative absorption (▵A) below 500 nm for ground state bleaching.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation